Male biased gene flow in banana pseudostem weevil (Odoiporus longicollis Oliver) as revealed by analysis of the COI-tRNA(Leu) COII region - Shankar, Pallavi; Kulkarni, Vishvas M.; Kumar, Lalitha Sunil (Genetica, 2015)
The genetic diversity amongst thirty weevils representing six Indian populations of banana pseudostem weevil i.e. Odoiporus longicollis (Oliver) was estimated by sequence analysis of the partial COI-tRNA(Leu)-COII region. The sequences exhibited AT bias typical of insect mitochondrial DNA which was highest in the first codon position of COI and in the third codon position of COII. There was no phylogeographic distribution of the populations. The Fu and Li's D and F tests were non-significant for this mitochondrial region. No Wolbachia infection was detected in any of the populations. The genetic differentiation amongst the populations was highly significant (p < 0.001; chi(2) = 123.333; df = 75), suggesting restricted gene flow between the populations. This result did not correlate with that obtained with nuclear rDNA markers i.e. ITS1 and ITS2, suggesting a male biased gene flow between the populations.
Keywords: Banana pseudostem weevil; COI-tRNA(Leu) -COII; Genetic differentiation; Male biased gene flow; Odoiporus longicollis (Oliver)